Approximation of solutions to evolution integrodifferential equations. (1996) - Bahuguna, D.; Srivastava, S. K.
Abstract : In this paper we study a class of evolution integrodifferential equations. We first prove the existence and uniqueness of solutions and then establish the convergence of Galerkin approximations to the solution.